Dispossession of land in Colombia: the infamous face of the economic reprimarization: To find the structural causes of the spoliation - Moreno López, William (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Less known than the expropriation of land, perpetrated by paramilitaries in Colombia since the end of the previous century, are the causal relationships underlying this phenomenon; In the perspective of contributing to the discussion in order to identify these structural causes, this paper examines the neoliberal model that, established in the country since 1990, works consistently with a new international division of production that results in the reprimarization of the Colombian economy, a scenario where land represents the most precious means of production that, as such, encourages dispossession, as this qualitative research concludes after an weighted documentary review.